Representasi Prilaku Sosial dalam Album Red Pill Blues Karya Maroon 5 - Dhyta Milla Augustine (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2023)
The title of this research is Representation of Social Behavior in the Red Pill Blues album Marron 5, which is to find out the social behavior contained in the song lyrics on the Red Pill Blues album. The purpose of this research is to find out the social differences between American's life and Indonesian's life to Maroon 5 music listeners by understanding the meaning contained in the song lyrics. The research method used in this research is descriptive qualitative, qualitative based on Anggito & Setiawan, while descriptive according to Rukajat. Approach The research in this study uses a social approach to analyze and determine the social behavior contained in the song lyrics represented by the author so that it affects his work, with a dynamic meaning theory based on Kecskes and Clark. The results of this study found social behavior contained in several song lyrics in the album Red Pill Blues by Maroon 5 in the songs entitled Lips on You and Best 4 U.